Birds eye view of Port of Spain, Trinidad - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, Trinidad, 2010)
This postcard provides an aerial view of the city of Port of Spain. In the distance the Port of Spain harbour can be seen.
Colour: Sepia (print); Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trinidad and Tobago--Aerial Views; Cities and towns--Trinidad and Tobago--Port of Spain; Harbors--Trinidad and Tobago